Literature Review: Children's Perspectives on Multiple Disabilities - Damaryana Nurhani; Eica Anjarwati; Faiza Aryareinita Safira; Tria Apriliani; Citra Ashri Maulidina (Indonesian Journal Publisher, 2025)
Children with multiple disabilities experience more than one type of developmental impairment that interacts and affects their communication, learning, and social participation. However, they are often understood through a deficit-based perspective, which limits recognition of their experiences and potential. This study aims to examine the perspectives of children with multiple disabilities through a systematic review of previous research. A qualitative descriptive literature review was conducted by analyzing 20 relevant journal articles from both national and international sources. Data were examined using thematic analysis to identify common patterns and shifts in perspectives. The findings indicate a shift from a limitation-focused approach to a more humanistic, contextual understanding. Children with multiple disabilities are recognized as active individuals with unique ways of communicating and interacting with their environment, even in the absence of verbal language. Responsive and inclusive environments, particularly the roles of families and educators, are essential in supporting children’s development and quality of life.